2008 IEEE Sensors 2008
DOI: 10.1109/icsens.2008.4716749
|View full text |Cite
|
Sign up to set email alerts
|

Piezo resistive thin film sensor system

Abstract: This paper presents the latest investigations of thin film sensor developments based on amorphous hydrogenated carbon films. The piezo resistive layer is deposited in a plasma enhanced chemical vapour deposition process in a thickness of 4-6 m. The advantage of this film is a excellent tribological behaviour with a hardness of 20-40 GPa and a coefficient of friction of 0,2 as it is well known from the diamond like carbon layers combined with a piezo resistive characteristic. This layer can detect loads without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Piezoelectric thin films are considered emergent materials for integration within Micro Systems Technology (MST) or Micro Electro Mechanical (MEM) devices. Plenty of research activities for the piezoresistive thin film has been shown worldwide [17][18][19][20]. While the strain sensitivity of piezoelectric is 50,000 times the one of piezoresistive thin film [14], piezoresistive thin film is appropriate in a lab setting to detect the moving objects that weights much less than the airplanes or moving vehicles in airport field.…”
Section: B Analog-to-digital Interfacementioning
confidence: 99%
“…Piezoelectric thin films are considered emergent materials for integration within Micro Systems Technology (MST) or Micro Electro Mechanical (MEM) devices. Plenty of research activities for the piezoresistive thin film has been shown worldwide [17][18][19][20]. While the strain sensitivity of piezoelectric is 50,000 times the one of piezoresistive thin film [14], piezoresistive thin film is appropriate in a lab setting to detect the moving objects that weights much less than the airplanes or moving vehicles in airport field.…”
Section: B Analog-to-digital Interfacementioning
confidence: 99%
“…The concepts of a smart bearing have also been discussed recently by Schirra, T. et al [28,29]. Other examples for sensor integration in mechanical components include feather key [30], fasteners [31,32], ball screw (e.g., [33,34]) and die (seen as part of the overall stamping system) [35].…”
Section: Introductionmentioning
confidence: 99%